Seroprevalence and associated risk factors for chlamydiosis, coxiellosis and brucellosis in sheep and goats in Borana pastoral area, southern Ethiopia - Tesfaye, Asamenew (BMC Vet Res, 2020)
BACKGROUND: Abortion is considered an important disease problem of small ruminants in Borana pastoral area. A cross-sectional study was conducted to estimate the prevalence and risk factors of chlamydiosis, coxiellosis (Q-fever) and brucellosis in small ruminants in selected districts of Borana zone. RESULTS: A total of 506 sheep and goats were tested using serological tests. Fifty (9.88%; 95% CI: 7.42, 12.82), 144 (28.46%; 95% CI: 24.56, 32.61) and none (0.00%; 95% CI: 0.00, 0.59) of them were positive for chlamydiosis, coxiellosis and brucellosis, respectively. History of abortion was recorded in 136 (32.00%; CI: 27.59, 36.67) of sheep and goats in the study area. The logistic regression analysis, however, showed that statistically significant difference ccurred among districts and between the species of small ruminants. The prevalence odd of antibodies against C. abortus was significantly lower in Miyo, Dire and Teltelle districts compared to Dillo. The odd of infection with this bacterium was lower in sheep than goats. Similarly the odd of infection with C. burnettii was significantly higher in Dillo district than the rest of the districts studied, higher in goats than sheep and higher in adult animals than young ones. CONCLUSION: High prevalence of abortion is observed in sheep and goats in the study area. High seropositivity of C. burnetii and C. abortus in both sheep and goats tested implies risks of human infection by both diseases. Thus, attention needs to be paid to further study of both diseases in animals and humans in the area.